Honey's antiviral research landscape: a 28-year bibliometric analysis (1996–2024) - Ismail, Che Muhammad Khairul Hisyam; Ismail, Azlini; Abdul Hamid, Azzmer Azzar; Mohd Abdul Razak, Mohd Ridzuan; Mokhtar@Makhtar, Khairani Idah; Lestari, Widya; Mustafa Al-Ahmad, Basma Ezzat (Academic Association of Pharmaceutical Sciences from Antofagasta (ASOCIFA), 2026)
Context: Honey, a natural bee product, has been widely used for its therapeutic properties, including potential antiviral effects.